In vitro antiurolithiatic effect of selected Prophetic medicines - Darnis, Deny Susanti; Abd Hamid, Shafida (2015)
Kidney stone is a disease that happens to many people in this world. There is possibility of a patient who has kidney stone will develop another. Thus, to prevent the recurrence of having kidney stone, there is an alternative treatment by using herbal plants. The proposed plants used in this experiment were based on some of the plants that have been described in book, healing with the medicine of Prophet by Imam Ibn Al-Qayyim Al-Jauziah. The plants were Aloe vera, Cymbopogon citratus, Lawsonia inermis, Nigella sativa, Punica granatum, Trigonella foenum-graecum (hulbah, حلبة), Hordeum vulgare L. (barley, sha’ir, الشعير), Apium graveolens var. dulce (celery, karafs, كرفس) and Vitis vinifera (grapevine, enab, عنب). The extractions of the plants were prepared by using water aqueous extraction. The tests were carried out by the crystallization of whole urine assay and determine the acute oral toxicity of L. inermis hydroalcohol extract and C. citratus aqueous extract in vivo. The antiurolithic method was conducted by induced the supersaturation of calcium oxalate in the urine by adding sodium oxalate solution. The extracts were put in the solutions and incubated at 37 °C for 30 min. The tube with no extract was used as control. The results were calculated based on the percentage of inhibition. The percentage of inhibition is measuring the plants extract that can prevent the early formation of kidney stone. The five plants showed positive result inhibits the prevention of supersaturation. However, the concentrations that inhibit the activities vary between the nine plants. There are effective concentrations and dose dependent that give effect on antiurolithiasis. The effective concentration of A. vera and P. granatum are at 0.25 mg/mL with the percentage of inhibition of 95% and 59%, respectively. The effective concentration for L. inermis is 0.5 mg/mL and the percentage of inhibition is 95%. The percentage of inhibition for C. citratus and N. sativa were increased or decreased by increasing the concentration (0.0625 to 1.0 mg/mL). T. foenum-graecum plant extract that can inhibit the early formation of kidney stone with the effective concentration is 0.125 mg/mL with the percentage of inhibition of 81.66 %. The effective concentration of H. vulgore is 0.5 mg/mL with the percentage of inhibition at 68.86 %. The most effective concentration from A. graveolens is 0.5 mg/mL with the percentage of inhibition at 74.05 %. V. vinifera extract showed the effective concentration at 0.0625 mg/mL with the percentage of inhibition 50.52 %. In conclusion, all plants showed the positive results in inhibiting the formation of early stage of kidney stone despite of different concentrations and the percentages of inhibition. It is also scientifically proven that single dose of hydroethanolic extract of L. inermis (henna) leaves can cause toxicity towards liver and kidneys of the mice and aqueous extract of C. citratus with regards to the massive high dose of 5000 mg/kg, are considered to be safe